COFFEE PROCESSING ASSISTANCE FOR HYANG ARGOPURO COFFEE FARMERS USING THE ABCD (ASSET BASED COMMUNITY DEVELOPMENT) APPROACH - Tamam, Badrut; Rohmad Agus Solihin; Ubaidillah Al Akhro; Nur Hafidhotul Ilma; Musfikil Wildan; Mochammad Sholeh; Syarifatul Amaliyah; Ifadatullailiyah; Firda Infitahul Mawarddah; Muhammad Aldin Hamdani (Universitas Djuanda, 2023)
Gunungsari Village, Maesan District is one of the villages in the Argopuro mountain region so that its natural potential is quite abundant, one of which is coffee. However, in terms of marketing, the community is only limited to selling green bean coffee. The focus of the chosen service is training and assistance related to coffee processing. The service location is located in Gunungsari Village, Maesan District, Bondowoso Regency. The approach used in this community service is the ABCD (Asset Based Community Development) approach, which starts with mapping the existing assets in Gunungsari village, followed by discussions with government officials and the community door to door. Then do a Focus Group Discussion (FGD). The FGD activities resulted in an agreement that the asset to be developed was coffee. The next step is to hold coffee processing training and assistance which aims to increase the selling price of coffee produced by farmers in Gunungsari Village..